2015
DOI: 10.7863/ultra.14.12076
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal Sonographic Features of a Double Aortic Arch

Abstract: A double aortic arch is a relatively uncommon anomaly occasionally associated with congenital heart disease or the chromosome 22q11 deletion. We report a case of prenatal diagnosis of a double aortic arch in which the sonographic features in the 3-vessel and trachea view are highlighted. A PubMed-based search was made to retrieve all cases of prenatal diagnosis of double aortic arch. A total of 13 articles and 35 cases were found. The average gestational age at diagnosis was 29 weeks. Six cases had associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 24 publications
(26 reference statements)
2
44
3
3
Order By: Relevance
“…We found that fetuses with a RAA forming a CVR have a low likelihood of CHD, with associated CHDs usually being minor, although conotruncal anomalies have been associated previously with RAA/LPDA/ALSA. Conversely, fetuses with a RAA not forming a CVR had a higher rate of associated complex CHD, most frequently a conotruncal anomaly. In our series, all cases with RAA/LADA/MI and one‐third of those with RAA/RDA/MI were associated with conotruncal CHD, which is consistent with both fetal and autopsy reports.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that fetuses with a RAA forming a CVR have a low likelihood of CHD, with associated CHDs usually being minor, although conotruncal anomalies have been associated previously with RAA/LPDA/ALSA. Conversely, fetuses with a RAA not forming a CVR had a higher rate of associated complex CHD, most frequently a conotruncal anomaly. In our series, all cases with RAA/LADA/MI and one‐third of those with RAA/RDA/MI were associated with conotruncal CHD, which is consistent with both fetal and autopsy reports.…”
Section: Discussionsupporting
confidence: 89%
“…We found that fetuses with a RAA forming a CVR have a low likelihood of CHD, with associated CHDs usually being minor, although conotruncal anomalies have been associated previously with RAA/LPDA/ALSA. Conversely, fetuses with a RAA not forming a CVR had a higher rate of associated complex CHD, most frequently a conotruncal anomaly.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…З розвитком пренатальної діагностики в нашому Центрі покращилася діагностика всіх ВВС, зокрема так званих дрібних аномалій, у тому числі й аномалій судин, таких як СК. Значним поштовхом до покращення пренатальної діагностики в 2011 році стало введення як обов'язкових проекцій трьох судин і трахеї, дуги аорти по довгій осі та високого поперекового зрізу черевної порожнини для визначення положення черевного відділу аорти [1][2][3][4]. Діагностика СК є важливою: хоча ця ВВС і вкрай рідко призводить до смерті, проте тривале не-діагностоване стиснення трахеї та стравоходу може спричинити інвалідизацію пацієнтів [5][6][7].…”
unclassified